BIRTH-MARKS OF RUSSIAN MENTALITY AND THE CULTURE OF INTERNATIONAL BUSINESS - A. P. Liferov (Vestnik MGIMO-Universiteta)
The paper deals with the analysis of typical features of Russian mentality, the so-called «birthmarks », and their influence upon the ways business is conducted in the global economic markets. The aim of the paper is to examine how historically determined elements of Russian business culture correlate with demands of contemporary international business practice. It is shown that Russian mentality and business, nurtured on the boarder-line between Western and Eastern cultures, possess a dual character. The paper shows the pendulum character of Russian business strategies in their interrelations with other countries. Taking into consideration foreign experts’ appreciation and attitudes the author distinguishes the most typical features of Russian mentality, which demolish the specific attractiveness of Russia. They include predominantly humanitarian, but not practically oriented mentality, changeable interest to foreign contacts, inability to follow treaties, numerous weak points in suggested projects, high expectations at the beginning, dubious character of approaches to problems, etc. The paper generalizes the image of the modern Russian entrepreneur and the way he is perceived abroad.